The Effect of Vitamin D Supplementation on Proteinuria in Type 2 Diabetes Mellitus Patients in DHQ Hospital Faisalabad - Atika Akram, Asad Mahmood Khan, Obaid Anwar, Muhammad Arif, Amin Anjum (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To evaluate the effect of Vitamin D supplementation on proteinuria in type 2 Diabetes Mellitus patients in attending DHQ Hospital Faisalabad . Materials and Methods: The design of this study was Quasi-experimental study design and the duration of this study was from December 2021 to June 2022. This study was conducted in the Department of medicine, in DHQ Hospital Faisalabad. Total 30 patients who were suffering from type 2 diabetes mellitus disease were enrolled.Their Vitamin D levels proteinuria, HbA1c and FBS level were evaluated. Oral Vitamin D 50,000 IU weekly was given to patients with Vit D deficiency for 8 weeks. At the end of 8 week vitamin D levels, FBS, HbA1c and proteinuria level were evaluated again. All the demographic details and study results were recorded on a predesigned data collection proforma. Results: Out of total 30 patients, 11 were male and 19 were female with mean age of 34.73±9.14 years. The most common age group was 41-50 years in which 36.7%, followed by age group of 31-40 years in which 33.3% and 30.0% patients were in age group of 41-50 years. The statistical difference between pre-intervention and post-intervention was calculated, and p-value was significant. In our study as Vit. D level increases while proteinuria decreases. Practical Implication: In diabetic patients its deficiency lead to a number of serious conditions such as ischemic heart disease, CKD and Diabetic nephropathy. Vit D play its role in the inhibition of the renin-angiotensin system. It also have a protective role in the kidney by preventing of glomerulosclerosis and anti-proteinuric effect. Conclusion: Vitamin D supplementation is helpful in decreasing proteinuria in Vit. D deficient T2DM patients. Keywords: Vitamin D, Proteinuria, Type 2 Diabetes Mellitus, Albumin Level, Proteinuria, Threatening Disorder.